2006
DOI: 10.1038/nmat1734
|View full text |Cite
|
Sign up to set email alerts
|

All-solid-state Z-scheme in CdS–Au–TiO2 three-component nanojunction system

Abstract: Natural photosynthesis, which achieves efficient solar energy conversion through the combined actions of many types of molecules ingeniously arranged in a nanospace, highlights the importance of a technique for site-selective coupling of different materials to realize artificial high-efficiency devices. In view of increasingly serious energy and environmental problems, semiconductor-based artificial photosynthetic systems consisting of isolated photochemical system 1 (PS1), PS2 and the electron-transfer system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
782
1
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,320 publications
(830 citation statements)
references
References 20 publications
15
782
1
10
Order By: Relevance
“…Additionally, it is often difficult to maintain long‐term stability and active state for the redox mediators, resulting in a decrease in reaction rates. To avoid these disadvantages, Z‐scheme systems without redox mediators have attracted much attention because they eliminate these limitations 7, 26…”
Section: Z‐scheme Systems With Shuttle Redox Mediatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it is often difficult to maintain long‐term stability and active state for the redox mediators, resulting in a decrease in reaction rates. To avoid these disadvantages, Z‐scheme systems without redox mediators have attracted much attention because they eliminate these limitations 7, 26…”
Section: Z‐scheme Systems With Shuttle Redox Mediatorsmentioning
confidence: 99%
“…Noble‐metal particles (such as Au, Ag) and reduced graphene oxide (RGO) were explored as electron mediators for the Z‐scheme system, and a high efficiency of the charge‐carrier separation and transport can be achieved at the interface of the two semiconductors 26, 47, 48…”
Section: Z‐scheme Systems With Solid State Electron Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] In 2006, Tada et al reported a first all-solid-state Z-scheme TiO 2 -Au-CdS system, which exhibits much higher photocatalytic activity than the two-component TiO 2 -CdS and Au-TiO 2 systems. 19 Nevertheless, the overall solar conversion efficiency of this system is limited because TiO 2 only absorbs UV light. In consideration of this issue, combining two visible-light-response photocatalysts in Z-scheme photocatalytic systems might be a promising strategy for the conversion of solar energy into H 2 fuel.…”
mentioning
confidence: 99%